MEDICINAL PLANTS OF SELECTED WETLANDS IN PANNISSERY AREA, THRISSUR DISTRICT, KERALA–A PRELIMINARY SURVEY - ATHIRA, K. R. (International Journal of Current Pharmaceutical Research, 2019)
Objective: Wetlands are vital ecosystem which provides livelihoods for millions of people who live within around them. Man depends on wetlands for most of his needs from time immemorial. The present study is a preliminary step for the identification of valuable medicinal plants in the wetlands of Pannissery area. This attempt was made since it is equally important to understand the traditional medicines and beliefs as well as to have scientific awareness for protection and conservation of the sewetlands. Methods: Frequent field visits were carried out from September 2018 to January 2019 to collect different Wetland medicinal plants in Pannissery area, Kandanassery Panchayath, Thrissur district. Plants were collected carefully with hand and identified by using the standard literature such as Flora of the Presidency of Madras by J. S. Gamble, 1915-1936. The collected plants were authenticated by a plant Taxonomist Dr. Udayan. P. S. from the Post Graduate and Research Department of Botany, Sree Krishna College, Guruvayur. Results: A slight alteration of the wetland may result in the disappearance or the extinction of these plants [1]. Conclusion: This will ultimately result in large scale economic loss in terms of the medicinal product. Apart from the loss of plants, this will also result in the loss of local knowledge on the medicinal properties of these plants which very often can't be retrieved. An attempt has been made to document some of the little known medicinal properties of wetland plants used by local community.